Reconfigurable pseudo biotic key encryption mechanism for cryptography applications - Murali Krishna, B.; Khan, Habibulla; Madhumati, G.L. (International Journal of Engineering and Technology, 2017)
Pseudo biotic cryptography will be an advanced crypto-analytic model, as it is presently increasing bimolecular computation, since its process energize and can verify future generation network computing. Nowadays, the data protection has become very important such that an unbreakable encryption technology should be designed in order to provide security for the data. A new paradigm in cryptography to secure information was introduced through biological structure called central dogma of molecular biology. DNA cryptographic system gains more popularity with enhanced features like, high storage capacity, security level, and more time to break the crypto system. This paper proposes new pseudo biotic DNA based crypto mechanism. This DNA computing created good path for storing large information, correspondence and high energy efficiency. The proposed method, message is converted to Deoxyribonucleic Acid (DNA), Messenger Ribonucleic acid (MRNA), and Transpose Ribonucleic acid (TRNA) standards. A part of converted message is spliced unsymmetrical to produce a random key at each stage. The sliced unsymmetrical key generation mechanism relies on the genetic information. The process involves in splicing the message and generating multiple sequence of keys from different stages which are random in order to enhance the degree of security. Cracking possibility of the algorithm is less due to pseudo random key generation mechanism and cipher both were merged in protein form. Proposed Algorithm utilizes less public key infrastructure, and communicated between Alice and Bob. Algorithm was designed, using Verilog HDL; Synthesized & Simulated in Vivado and hardware implementation is targeted to Zync FPGA architecture.Â